Effect of Educational Intervention on Knowledge and Attitude Toward Consanguineous Marriage among Secondary Level Students - Ghale, Alina; Shrestha, Sarala (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Consanguineous marriage (CM) is an allowed and preferred practice among some ethnic groups in Nepal. Such a union puts couples at higher risk of having offspring with genetic disorders, including autosomal recessive diseases and congenital malformations. The objective of this study was to assess the effect of educational intervention on knowledge and attitude towards CM among secondary-level Mongolian students. Methods: A quasi-experimental pretest-posttest non-equivalent group study was conducted among students in grades 9 - 12 of two schools in Dhading, with one school as the experimental group (N = 69) and another as the control group (N = 45). Educational intervention on CM was provided to the experimental group through an interactive lecture method. Pretest and posttest data were collected in both groups by using a validated and pretested selfadministered questionnaire. Data were analyzed using descriptive statistics. Results: In the experimental group, most (87.0%) participants had an inadequate level of knowledge in the pretest, whereas in the posttest, most (85.5%) had adequate knowledge. In the control group, both during pretest and posttest, most (i.e. 82.2% and 78.6%, respectively) had inadequate level of knowledge. In the experimental and control groups during the pretest most of the participants (87.0% and 88.9%, respectively) had a negative attitude. In contrast, in the posttest, the negative attitude decreased to 46.4% in the experimental group, and in the control group the attitude level decreased only slightly to 84.4%. Unpaired t-test computed on pretest knowledge of the experimental group and control group showed no significant difference (t = 0.968, p > 0.05), whereas the posttest knowledge between the two groups revealed a statistically significant difference (t = 23.643, p < 0.05). Conclusions: The educational intervention package effectively increases knowledge and changes attitudes towards consanguineous marriage among secondary-level students.